ZnO-TiO2 composite formed by mixed oxides via polyol - Murador Filho, Aureo [UNESP]; Dos Santos, Dayse Iara [UNESP]; Kussuda, Marcos Yukio [UNESP]; Zanatta, Camilla dos Santos [UNESP]; Kim, Jae Geon; Shi, Don Qui; Dou, Shi Xie (Trans Tech Publications Ltd, 2012)
Among the researches on preparation and test of nanostructured materials, titanium dioxide and zinc oxide have been the most frequent studied oxides. In order to extend their properties, composites have been prepared using three different methods: Polyol Method, Sol-gel Process and a combination of the two processes (hybrid process). Recent research showed best properties in composite materials than in pure oxides. In this work is presented the preparation and the structural characterization of ZnO-TiO2 composite nanostructures to be tested for their performance in electrocatalysis and in further trial on photovoltaic cells.
Keywords: zinc oxide; titanium oxide; composite; spectroscopy; thermal analysis; XRD